Potencial de inundação na bacia hidrográfica do Rio Jucu/ES, por meio de parâmetros morfométricos e índices SL - Cruz, Edimundo Almeida da (2015)
The morphometric research applied to river basin Jucu / ES enabled the survey and characterization of the geometric indicators (zonal, linear and hypsometric) and SL Indices (Slope-Lenght Index). Systemic analysis was effective for expeditious diagnosis of areas susceptible to flooding, enabling reliable inferences about the hydromorphological behavior of this river system, based on the Dynamic Equilibrium Theory proposed by Hack (1973). The finding of small SL values over several flood basins of Jucu river (CJBN, CJBS, CJBC), less than k / 2, showed the presence of portions inclined smooth design or plan, so areas susceptible to flooding when runoffs greater than the full margins. The comparison between the SL and the other indexes and morphometric parameters shows that for the flooding phenomenon, the SL index appears more pragmatic and effective than the others, since the interpretation of results occurs concomitantly with analysis of the longitudinal profile, and as the assumptions river hydraulics processes described by Leopold and Maddock (1953).